Process optimization of oyster mushroom (Pleurotus ostreatus) chips using response surface methodology - Bulagao, Bebviet Franz R.; Villarino, Casiana Blanca J. (Quezon City: College of Home Economics, University of the Philippines, 2018.)
The objective of this study was to establish the process of vacuum fried oyster mushroom (Pleurotus ostreatus). It specifically aimed to determine the effects of frying time and frying temperature on the physico-chemical properties (i.e., water activity, moisture content), and consumer acceptability (i.e., appearance, color, oiliness, crunchiness, taste and overall acceptability) of mushroom chips using response surface methodology; and optimize and verify the process for vacuum fried oyster mushroom. Frying time and frying temperature had significant (p<0.05) linear and quadratic effects on the physico-chemical properties of the mushroom chips. On the other hand, consumer acceptability of the samples was significantly (p<0.05) influenced (i.e., linear and quadratic) by frying temperature. The optimum parameters for vacuum frying of oyster mushroom were 100-120.84°C for 1 to 5.6 min. Verification studies showed that the generated models were able to predict the responses accurately. Results of the study present the potential of vacuum fried oyster mushroom as a healthier alternative to fried snacks available in the market.
Submitted January 2018.
Thesis (B.S. Food Technology)---University of the Philippines Diliman.
Keywords: Oyster Mushroom